Antecedents of Webrooming in Omnichannel Retailing - Kleinlercher, Kristina; Linzmajer, Marc; Verhoef, Peter C.; Rudolph, Thomas (Frontiers in Psychology, 2020)
Although webrooming has become common practice in omnichannel consumer behavior, only a few empirical studies have managed to shed light on the phenomenon. With this research work, we aim to investigate important antecedents of webrooming. We base our conceptual framework on anticipated utility theory and expect that customers’ anticipated utility from using the physical store versus the online store for purchase can be predicted by four groups of antecedents: psychographic variables, shopping motivations, channel-related variables, and product-related variables. With the help of a data set from a large cross-national online survey in which 1497 customers reconstruct their last purchase journey, we differentiate webroomers from pure online shoppers. In addition, we disentangle customers who used retailer-owned, competitor-owned, and independent touchpoints along the search and purchase phase of the customer journey in order to characterize webroomers in an omnichannel context and assess their prevalence in different countries and industries. Our insights on the characteristics and antecedents of webrooming help retailers to detect and better understand the psychology behind the webrooming phenomenon from a consumer perspective in an omnichannel retailing environment. In addition, results from our exploratory analysis on the positive association between webrooming and customer spending contribute to research and practice by providing first evidence on the economic value of webrooming.